Meat inspection and cultural isolation of mycobacteriaas predictors of bovine tuberculosis in Ibadan (2007)
In order to ascertain the effectiveness of meat inspection as against the conventional culture method in the confirmation of tuberculosis in cattle slaughtered at Bodija abattoir. Ibadan; a study to assess these two methods in their ability to diagnose bovine tuberculosis was carried out. In all. 290 cattle were inspected at the abattoir out of which 182 had military nodules and granulomatous tubercles in the different organs and their associated lymph nodes which are suggestive of tuberculosis. One hundred and fifty-nine (54.8%) animals were confirmed to have tuberculosis based on the mycobacterial culture. The sensitivity and specificity results of the postmortem examination vis-a vis the culture were 100% and 82.4% respectively; while the Positive Predictive Value (PPV) and the Negative Predictive Value (NPV) were 87.4% and 100% respectively. This study therefore confirms that with proper meat inspection. a large proportion of tuberculosis cattle can be identified at postmortem. Hence. more emphasis should be directed at the improvement of meat inspection Services in Nigeria since there are no available laboratory facilities for the diagnosis of bovine tuberculosis in the abattoirs